Having it all? Transferring community-oriented research principles to teaching and learning to develop better university engagement. Issue 1 (1st January 2017) - Adshead, Maura; Quillinan, Bernie
Abstract: There are increasing demands on universities to develop more meaningful linkages with local communities – from government, from citizens and taxpayers, and from students. But the incorporation of community-oriented praxis into the university mission is not straightforward and requires a significant re-orientation away from 'traditional' organizational norms regarding teaching and research. Where community practice involves students, there is a burgeoning literature on situated learning, service learning and problem-based learning; but where community practice relates to research, the literature tends to be very much more disciplinary oriented and the sources are commensurately disparate. Discussions about community perspectives, however, are typically located in another set of literatures altogether. In order to address this deficit, this article reviews the literature on community-oriented research with the intention of providing a more holistic view of the common concerns and issues that arise when universities move their work into communities. This article reveals that – despite different disciplinary origins – the varied literature on community-oriented research illustrates the evolution of consistent principles for good practice. Moreover, it argues that community-oriented research principles provide praxis guidelines for university engagement in communities that are often absent in the literature on teaching and learning or civic engagement. The article then presents a case study of the evolution an integrated institutional response, which combines community-oriented research approaches to teaching and learning and civic engagement, being developed at the University of Limerick, Ireland.